Inhibition of Microglial TGFβ Signaling Increases Expression of Mrc1 - von Ehr, Alexander; Attaai, Abdelraheim; Neidert, Nicolas; Potru, Phani Sankar; Ruß, Tamara; Zöller, Tanja; Spittau, Björn (Frontiers in Cellular Neuroscience, 2020)
Microglia are constantly surveying their microenvironment and rapidly react to impairments by changing their morphology, migrating towards the stimuli and adopting gene expression profiles characterising their activated state. Increased expression of the M2-like marker Mannose receptor 1 (Mrc1) which is also referred to as CD206 in microglia has been reported after M2-like activation in vitro and in vivo. Mrc1 is a 175 kDa transmembrane pattern recognition receptor which binds a variety of carbohydrates and is involved in pinocytosis and phagocytosis of immune cells including microglia and thought to contribute to a neuroprotective microglial phenotype. Here, we analysed the effects of TGFβ signalling on Mrc1 expression in microglia in vivo and in vitro. Using C57BL/6 wild type- and Cx3cr1CreERT2:R26-YFP:Tgfbr2fl/fl mice-derived microglia, we show that silencing of TGFβ signalling results in upregulation of Mrc1 whereas recombinant TGFβ1 induced delayed downregulation of Mrc1. Furthermore, chromatin immunoprecipitation experiments provided evidence that Mrc1 is not a direct Smad2/Smad4 target gene in microglia. Together, our data indicate that changes in Mrc1 expression after activation or silencing of microglial TGFβ signalling are likely to be mediated by modifications of secondary intracellular signalling events influenced by TGFβ signalling.